Novel DNA fluorescence probes based on N-[5-(11-functionalised-undecylamino)-9H-benzo[a]phenoxazin-9-ylidene]propan-1-aminium chlorides: synthesis and photophysical studies - Alves, Carla M. A. (2011)
Fluorescent benzo[a]phenoxazinium chlorides possessing undecylamino chains with functionalised ending-groups (hydroxyl, carboxylic acid and the ester group) as substituents at the 5-position of the heterocycles were successfully synthesised and characterised. These compounds were used in photophysical studies with DNA, and compared to the corresponding analogue with a non-functionalised terminal (methyl group). It was found that the functionalised terminal exerts a dramatic influence on the type of interaction with the hydroxyl group promoting intercalation, while the ester group promotes groove binding.